Big Data Analysis: How Public Response to Poverty Eradication Programs in Indonesia during COVID-19 Pandemic? - Khotimah, Dian Rizqi Khusnul (UIN Sunan Ampel Surabaya, 2021)
Poverty eradication is the main focus of the first Sustainable Development Goals (SDGs), namely 'No Poverty'. Nationally, poverty eradication is also implied in the 2020-2024 National Medium-Term Development Plan (RPJMN) on the first and second agendas. These are economic resilience and reducing disparities between regions. Various government programs are implemented to reduce poverty. The benefits obtained by the target community need to be measured to reflect the program's success and for government evaluation. Big data through social media analysis can be empowered to gain public perceptions of poverty eradication programs. Therefore, in this study, the Twitter social media analysis approach will be used to obtain public responses regarding various poverty eradication programs in Indonesia during the COVID-19 pandemic, especially the Family Hope Program (PKH or Program Keluarga Harapan), Cash Intensive Work (PKT or Padat Karya Tunai), Direct Cash Assistance (BLT or Bantuan Langsung Tunai), and Pre-Employment Cards (Kartu Prakerja). Those data were analyzed using the text mining method. The results of this study indicate that the public response generally accepts and supports the four poverty eradication programs in Indonesia. Those analysis results can be used as evaluation material and input for the Government to make the following policy.